2020
DOI: 10.1002/etc.4720
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Different Zinc Oxide Nanomaterials at 3 Trophic Levels: Implications for Development of Low‐Toxicity Antifouling Agents

Abstract: Because zinc oxide (ZnO) nanomaterials are used in antifouling and antibacterial solutions, understanding their toxic effects on different aquatic organisms is essential. In the present study, we evaluated the toxicity of ZnO nanoparticles of 10 to 30 nm (ZnONPI) and 80 to 200 nm (ZnONPII), ZnO nanorods (width 80 nm, height 1.7 µm) attached to the support substrate (glass, ZnONRG) and not attached (ZnONRS), as well as Zn2+ ions at concentrations ranging from 0.5 to 100 mg/L. Toxicity was evaluated using the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 60 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…The dose-dependent cytotoxicity of ZnONPs synthesized from Hyphaene thebaica towards brine shrimp was described by Mohamed et al [91]. Dobretsov et al [92] showed that the toxicity of ZnONPs towards Artemia salina depends on the morphology and concentration of ZnONPs, where ZnO nano-rods (width 80 nm) were least toxic. Our results showed the moderately toxic nature of ZnONPs at 300 µL concentration, which could be further reduced at lower concentrations.…”
Section: Caspase-3 Gene Expression and Caspase-3/7 Activitymentioning
confidence: 91%
“…The dose-dependent cytotoxicity of ZnONPs synthesized from Hyphaene thebaica towards brine shrimp was described by Mohamed et al [91]. Dobretsov et al [92] showed that the toxicity of ZnONPs towards Artemia salina depends on the morphology and concentration of ZnONPs, where ZnO nano-rods (width 80 nm) were least toxic. Our results showed the moderately toxic nature of ZnONPs at 300 µL concentration, which could be further reduced at lower concentrations.…”
Section: Caspase-3 Gene Expression and Caspase-3/7 Activitymentioning
confidence: 91%
“…This study opens up new dimensions regarding the positive impact of microplastics at low concentration, where they lessen the toxic effects of co-pollutants in the marine ecosystem. Recent studies confirm that ZnO nanoparticles can severely affect marine algae [12,[18][19][20]. There are also reports clearly showing the…”
mentioning
confidence: 93%
“…52 The cytotoxicity of the NPs was much lower compared to a published mono-cultured cell type than that observed in the 3D spheroids. 53,54 Thus, as suggested, 2D systems may overestimate chemical toxicity, ascribable to the absence of 3D organization, and confer some mechanical resistance to cytoskeletal disruption.…”
Section: Discussionmentioning
confidence: 92%